Peran Intervensi Pemerintah dalam Menstabilkan Nilai Tukar: Studi Kasus Indonesia, Jepang, dan Turki dalam Konteks Ekonomi Global - Talitha Tsaqif Salsabila Salsabila (Business Finence Analyst Co.,, 2024)
In the context of the global economy, this research analyzes the role of government intervention in stabilizing currency exchange rates in Indonesia, Japan and Türkiye. This study uses a quantitative approach to look at the different monetary policies implemented by the governments of these three countries to overcome changes in exchange rates caused by international markets. To determine how effective government intervention is in maintaining economic stability, data collected from various sources, including economic statistics and central bank reports, is analyzed. The research results show that government intervention has a significant effect on the exchange rate, but its effectiveness varies depending on the economic and political conditions of each country. It is hoped that these findings will help policymakers create better strategies to stabilize the exchange rate amidst ever-changing global economic challenges.